Reversible suppression of autophagy in a mouse model reveals neuronal resilience - Tomoya Eguchi; Manabu Abe; Takuya Tomita; Hideaki Morishita; Yasushi Saeki; Kenji Sakimura; Kenji F. Tanaka; Noboru Mizushima (Science, 2026)
Impairments in intracellular quality-control mechanisms, including autophagy, affect neuronal integrity and function. Despite numerous studies aimed at slowing neuronal deterioration, it remains unclear whether neuronal function and intracellular quality can be restored once impaired. We developed a mouse model in which autophagy could be rapidly and reversibly regulated to investigate the reversibility of such defects. Suppressing autophagy led to proteome and transcriptome changes, inclusion body accumulation, and axonal swelling, all of which were largely ameliorated after autophagy restoration. Consistent with these cellular abnormalities, autophagy suppression induced motor and cognitive dysfunction, which was also reversed on autophagy restoration. Our findings elucidate the potential resilience of neuronal function and quality enabled by intracellular clearance.